Molecular epidemiology and antimicrobial resistance phenotype of paediatric bloodstream infections caused by Gram-negative bacteria - Lipworth, S; Vihta, K; Davies, T; Wright, S; Tabirao, M; Chau, K; Vaughan, A; Kavanagh, J; Barker, L; George, S; Segal, S; Paulus, S; et al. (Springer Nature, 2022)
Background Gram-negative organisms are common causes of bloodstream infection (BSI) during the neonatal period and early childhood. Whilst several large studies have characterised these isolates in adults, equivalent data (particularly incorporating whole genome sequencing) is lacking in the paediatric population.